(untitled) (The Research of Medical Science Review, 2025)
Background: Acute ischemic stroke (AIS) patients have an increased risk of atrial fibrillation (AF), which can worsen stroke outcomes. Some studies report higher frequencies of AF, but these findings vary across populations. This study was designed to provide a clearer conclusion on the prevalence of AF in AIS patients. By analyzing frequency and risk factors, the study aims to clarify the relationship between AF and AIS, aiding in more informed clinical management. Objective: To compare Duration: Six months w.e.f. 03-08-2024 to 02-02-2025. Methodology: A total of 140 patients with acute ischemic stroke, meeting the inclusion criteria, were enrolled at Punjab Rangers Teaching Hospital, Lahore, after obtaining informed consent. A 12-lead ECG was performed on each patient to confirm atrial fibrillation (AF), which was classified as acute, paroxysmal, persistent, or permanent. To minimize bias, all ECGs were conducted by the same staff using the same machine. Findings were reviewed by a senior consultant, and confounding variables were controlled by exclusion. Patients received treatment as per the department’s standard protocol. Results: The study included 140 patients with a mean age of 66.70 ± 8.28 years. Most participants were aged 55-70 years (67.1%), and 52.1% were male. The mean BMI was 27.54 ± 3.36 kg/m², with 54.3% overweight and 25.7% obese. A family history of AF was reported in 6.4%. AF was present in 24.3% of patients, with higher frequencies observed in older age groups, males, obese individuals, and those with a family history, though statistical significance was not reached. Conclusion: In conclusion, this study found that atrial fibrillation (AF) was present in 24.3% of acute ischemic stroke (AIS) patients. Although a higher frequency of AF was observed in older age groups, males, obese individuals, and those with a family history of AF, statistical significance was not achieved in any subgroup, possibly due to the small sample size. Therefore, patients with AIS must be screened for AF to enable anticipatory management and improve clinical outcomes.